Teaching Presence vs. Student Perceived Preparedness for Testing in Higher Education Online English Courses During a Global Pandemic? Challenges, Tensions, and Opportunities - Morales, Ronald; Frenzel, Mónica; Bravo, Paula Riquelme (Frontiers in Psychology, 2022)
In the context of a global pandemic that started in 2020, the Chilean higher education institution Universidad Andrés Bello (UNAB) faced the challenge of giving continuity to its already established blended program for English courses while also starting the implementation of a high-stakes certification assessment for its students using the Test of English for International Communication (TOEIC) Bridge. This study sought to evaluate how much of a mediating factor online teaching presence could be in the context of test preparation within a language course in aspects related to autonomous learning and perceived learning outcomes. A mixed-methods approach was used. It included a survey applied to 1,642 eligible students of the English program. These quantitative data were complemented with students’ comments and teacher interviews. After triangulating quantitative and qualitative data, teaching presence was clearly perceived to be a relevant aspect of the online experience in the studied courses. However, both students’ and teachers’ voices evidenced pervasive challenges and tensions that hinder the potentially transformative benefits that online learning is expected to bring about.